Frictional Performance and Temperature Rise of a Mining Nonasbestos Brake Material during Emergency Braking - Jiusheng Bao; Zengsong Li; Dongyang Hu; Yan Yin; Tonggang Liu (Advances in Materials Science and Engineering)
By simulating emergency braking conditions of mine hoisters, tribological experiments of a mining nonasbestos brake material sliding on E355CC steel friction disc investigated a pad-on-disc friction tester. It is shown that, under combined influence of braking velocity and pressure, the lubricating film and micro-convex-apices on wear surface would have complex physicochemical reactions which make the instant friction coefficient rise gradually while the instant surface temperature rises first and then falls. With the antifriction effect from lubricating film and the desquamating of composite materials, the mean friction coefficient decreases first, then rises, and decreases again with the increasing of initial braking velocity. And with the existence of micro-convex-apices and variation from increment ratio of load and actual contacting area, it rises first and then falls with the increasing of braking pressure. However, the mean surface temperature rises obviously with the increasing of both initial braking velocity and braking pressure for growth of transformed kinetic energy. It is considered that the friction coefficient cannot be considered as a constant when designing brake devices for mine hoisters. And special attention should be paid to the serious influence of surface temperature on tribological performance of brake material during emergency braking.